Bloody Mary. Volume 5 - Samamiya, Akaza (Shojo beat manga., 2016)
A blood-pounding tale of an unorthodox alliance between a vampire and an exorcist. "Bloody" Mary, a vampire with a death wish, has spent the past 400 years chasing down a modern-day exorcist named Maria who is thought to have inherited "The Blood of Maria" and is the only one who can kill Mary. To Mary's dismay, Maria doesn't know how to kill vampires. Desperate to die, Mary agrees to become Maria's bodyguard until Maria can find a way to kill him. Maria and Mary go to England to meet the mentor who taught Shinobu how to fight vampires, hoping that he might hold the answers that Maria seeks. But he's already gone by the time they arrive, and they are met, instead, by a blonde beauty in a lab coat. Meanwhile, the familiar scenery stirs up long-repressed memories Mary had once forgotten.